A new trapdoor spider of the genus Actinopus (Araneae, Mygalomorphae, Actinopodidae) from Argentina - Ríos-Tamayo, Duniesky; Goloboff, Pablo A. (Zootaxa, 2025)
A small species of the spider genus Actinopus Perty 1833 from Copo National Park in Argentina is described—Actinopus chilikuti sp. nov. The new species belongs to a small group that in Argentina previously comprised three morphologically homogeneous species. Detailed morphological descriptions of both sexes, illustrations and geographic distribution of the new species are presented.